2020
DOI: 10.1038/s41598-020-73486-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive temporal detection of early retinal vascular changes during diabetes

Abstract: Diabetes associated complications, including diabetic retinopathy and loss of vision, are major health concerns. Detecting early retinal vascular changes during diabetes is not well documented, and only few studies have addressed this domain. The purpose of this study was to noninvasively evaluate temporal changes in retinal vasculature at very early stages of diabetes using fundus images from preclinical models of diabetes. Non-diabetic and Akita/+ male mice with different duration of diabetes were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 79 publications
0
9
0
1
Order By: Relevance
“…This outcome also supported the data obtained for VEGF-A release. 54 , 55 It is important to note that B and Ca release from BcHA resulted in a more efficient temporal modulation on VEGF-A as well as expression of angiogenic genes, such as eNOS and VEGFR2, compared to Ctrl or Ca amount P released from cHA. Therefore, it could be speculated that there should be a synergistic effect of B and Ca in rapid vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome also supported the data obtained for VEGF-A release. 54 , 55 It is important to note that B and Ca release from BcHA resulted in a more efficient temporal modulation on VEGF-A as well as expression of angiogenic genes, such as eNOS and VEGFR2, compared to Ctrl or Ca amount P released from cHA. Therefore, it could be speculated that there should be a synergistic effect of B and Ca in rapid vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…The ratios calculated were neovascular area to retina area 49 . And branches of retinal blood vessels were evaluated using Angiogenesis Analyzer plug‐in in ImageJ software 50 …”
Section: Methodsmentioning
confidence: 99%
“…49 And branches of retinal blood vessels were evaluated using Angiogenesis Analyzer plug-in in ImageJ software. 50…”
Section: Retinal Flat-mounts and Lectinstainingmentioning
confidence: 99%
“…More recently, Saghiri et al evaluated temporal retinal vascular changes in the early stages of diabetes using fundus images from male Akita mice. Although changes of the vascular network such as segments, length, number of branches and junctions were reported, the study did not evaluate the geometrical changes observed in clinical studies (Saghiri et al, 2020).…”
Section: Animal Models Of Diabetes Associated Microvascular Diseasesmentioning
confidence: 99%